(untitled) (Research, Society and Development, 2020)
Contemporary times require an education that encourages students to think in depth and reflection, and that changes in time in professional qualification in physiotherapy have been requested so that curricula meet the specific needs of regions, such as the expectations of documents and students, including a teaching, research, and extension passage were thus prepared as National Curriculum Guidelines (NCG). Also, as higher education institutions (HEIs), they must apply the organizational environment that allows them to know the work environment and the quality level practiced at the HEIs. The aim of the present study was to analyze the perception of the physiotherapy students of two institutions, about the influence of the NCG implementation and the organizational environment aspects in their academic qualification. The present research had a quantitative and qualitative approach. One sample consisted of students from a public and a private institution who answered a questionnaire and the data were analyzed descriptively. Verify that the course and course content meet student expectations, teamwork and relationship to documents were critical to quality education and innovations in teaching methodologies. The opinion of the students differed as to the time of the practical disciplines, infrastructure, performance in the three levels of attention and search for promotion, prevention and rehabilitation, and the perception of the students of the public institution of agreement during private practice totally agreed. It can be concluded the implementation of NCG, as well as the organizational environment influences the academic formation.